Sociodemographic Aspects and Healthy Behaviors Associated With Perceived Life Satisfaction in Health Professionals - Esther Durand-Sanchez; Carlos Ruiz-Alvarado; Ricardo Contreras-Valderrama; Wilter C. Morales-García; Oscar Mamani-Benito; Salomón Huancahuire-Vega; Jacksaint Saintila; Mardel Morales-García; Percy G. Ruiz Mamani (SAGE Publishing, 2023)
Background: Life satisfaction is a determining factor for the improvement of mental and physical health. Health care workers are a vulnerable population to suffer alterations in the factors that affect life satisfaction. Determining the influence of these factors on quality of life is important for their proper management. Objective: To examine sociodemographic factors and healthy behaviors influencing life satisfaction in Peruvian professionals. Methods: A cross-sectional study was conducted with 506 health care workers, who had a mean age of 40.34 years (SD = 10.39). A sociodemographic questionnaire, sleep quality, physical activity, eating habits, and life satisfaction were used. A regression model was fitted with the life satisfaction variable as the dependent variable. Results: In multivariable analysis, age (β = −.938, P  < .01) and perception of poor health status (β = −4.743, P  < .001) were found to be associated with lower life satisfaction. On the other hand, higher university education level (β = 1.667, P  < .001), absence of smoking (β = 3.202, P  < .01), absence of depressive symptoms (β = 3.390, P  < .001), interest in daily activities (β = 3.503, P  < .05), good sleep quality (β = 1.027, P  < .01), a high frequency of physical activity (β = 1.056, P  < .01), and healthy eating are variables associated with higher life satisfaction. Conclusion: Sociodemographic aspects such as age and the perception of poor health are associated with lower life satisfaction. On the other hand, healthy behaviors such as absence of smoking, absence of depressive symptoms, interest in daily activities, good quality of sleep, high frequency of physical activity, and a healthy diet were associated with higher life satisfaction.